From Face-to-Face Learning to E-Learning Platforms: The Inevitability of Transition and Implementation Challenges (Sebha University Conference Proceedings, 2025)
This paper deals with the topic of the transformation from traditional face-to-face learning to E-Learning Platforms in the Algerian university. Our goal is to highlight  one of the most recent educational environments created by the technological development and rapid global changes, and imposed by Covid 19 pandamic; namely, e-learning platforms. The study examines their reality and the challenges facing their use in Algerian universities.The importance of this study lies in analyzing the factors driving this transformation and exploring its inevitability in light of technological and knowledge developments, while diagnosing the difficulties facing the activation of electronic platforms in the educational process from the professors' perspective. To study this subject, we employed a descriptive analytical methodology to analyze the factors driving the adoption of electronic platforms in education and to classify the difficulties facing their implementation at the institutional, human, and technical levels.The research concluded that the transition to education through electronic platforms has become an imperative imposed by the data of the digital age, global trends towards the digitization of education, and the requirements of improving the quality of higher education, and was reinforced by the Covid-19 pandemic, which showed the limitations of traditional education in the face of exceptional circumstances. The research also revealed multiple challenges facing this transformation, such as: Weak technological infrastructure, deficiencies in the digital competencies of professors and students, and the absence of clear e-learning strategies.